Characterization and phylogenetic analysis of the mitochondrial genome of Schizothorax taliensis, a national-protected fish in China. Issue 2 (3rd July 2018) - Rui, Xiao; Sun, Xiao-Qing; Li, Shang-Qi; Li, Jiong-Tang
Abstract: Schizothorax taliensis is a national key protected fish in China. The mitochondrial genome of S. taliensis is 16, 578 bp in length and includes two ribosomal RNA genes, 22 tRNA genes, and 13 protein-coding genes. The phylogenetic analysis showed that S. taliensis belongs to Cyprinidae family and is closely related to other Schizothorax fish. This mitogenome will contribute to the further conservation and genetic studies of this endangered fish.